Safe Care for Maternal Substance Use and Neonatal Drug Withdrawal. Issue 5 (September 2015) - Simpson, Kathleen Rice
Abstract : As maternal use and abuse of opioids and other prescription drugs increases, plans are needed for safe care in the inpatient setting for babies with symptoms of drug withdrawal. Staffing a well-baby nursery with a registered nurse to care for one newborn with withdrawal symptoms can negatively affect overall unit staffing and productivity budgets, but based on the population served and recent history of positive maternal and newborn drug screens, predictions can be made for staffing needs and staffing budgets adjusted accordingly.